Gender and cervical artery dissection - Metso, Antti Juhani; Lichy, Christoph; Kloss, Manja; Brandt, Tobias; Grond-Ginsbach, Caspar (European journal of neurology, 2012)
Background and purpose: To analyze previously established gender differences in cervical artery dissection (CeAD). Methods: This case-control study is based on the CADISP (Cervical Artery Dissection and Ischemic Stroke Patients) population comprising 983 consecutive CeAD patients (mean age: 44.1 ± 9.9 years) and 658 control patients with a non-CeAD ischemic stroke (IS) (44.5 ± 10.5 years). Results: Cervical artery dissection was more common in men (56.7% vs. 43.3%, P < 0.001) and men were older (46.4 vs. 41.0 years, P < 0.001). We assessed putative risk factors for CeAD including vascular risk factors, recent cervical trauma, pregnancies, and infections. All gender differences in the putative risk factors and outcome were similar in the CeAD and the non-CeAD IS groups. Conclusion: Our analysis of the largest collection of CeAD patients to date confirms male predominance and differences in age at dissection between men and women. Gender differences in putative risk factors may explain the higher frequency of CeAD in men and their older age, but the putative risk factors are probably not specific for CeAD.
First published: 10 December 2011
Gesehen am 22.11.2018